All-inorganic perovskite nanocrystals: next-generation scintillation materials for high-resolution X-ray imaging. Issue 3 (10th January 2022) - Lu, Lu; Sun, Mingzi; Wu, Tong; Lu, Qiuyang; Chen, Baian; Huang, Bolong
Abstract : This review summarizes the recent research progress in all-inorganic perovskite nano-scintillators in terms of their potential applications in X-ray imaging and provides references on scintillation performance control for future material design. Abstract : With super strong penetrability, high-energy X-rays can be applied to probe the inner structure of target objects under nondestructive situations. Scintillation materials can down-convert X-rays into visible light, enabling the reception of photon signals and photoelectric conversion by common sensing arrays such as photomultiplier tubes and amorphous-Si photodiode matrixes. All-inorganic perovskite nanocrystals are emerging photovoltaic and scintillation materials, with tremendous light-conversion efficiency and tunable luminous properties, exhibiting great potential for high-quality X-ray imaging. Recent advancements in nanotechnology further accelerate the performance improvement of scintillation materials. In this review, we will provide a comprehensive overview of novel all-inorganic perovskite nano-scintillators in terms of potential applications in low-dose X-ray medical radiography. Compared with conventional scintillators, the merits/drawbacks, challenges, and scintillation performance control will be the focus of this article.